วิธีฮิวริสติกสำหรับการจัดสรรสายพานลำเลียงสัมภาระขาเข้า - สันทัศน์ ไชยเวช (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This thesis proposes to develop a heuristic method to solve problems of the allocation of inbound baggage carousels daily. This is to replace the current work which officers have to allocate inbound baggage carousels by themselves for 24 hours. The process is divided in to five main steps. The first step is to prepare data by input the weekly plan data and real-time data that have ETA in 60 minutes in advance to refresh the Estimated Time of Arrival: ETA. Second is consider whether there is any wrong conditions, if so, the incorrect flight will be removed from the belts. The third step is to create the wrong condition flight to the Assignment Cost Matrix: ACM by using overlapping time when need to allocate baggage carousels and set a very high cost for the fault conditions. The last step is to allocate for the fault condition by applying the Insertion Method and the Hungarian Method which have 3 key performance indices. Including the baggage carousels must be allocated according with the pit aircraft, the allocation must be provide the minimum joint, and requires the minimum number of changing the allocation. The study with the actual data shows that both of developed heuristic methods outperform the current work. In both cases, no fault allocation condition presented. The Hungarian Method reduces overlapping time by 39.31% and the Insertion Method reduces overlapping time by 29.42%. The time process is not long so this is ready for the expansion in the future. The conclusion is that the Hungarian Method is suitable for solve the inbound baggage carousels assignment problem .